RELIGIOUS COUNSELING ASSISTANCE FROM THE QURAN PERSPECTIVE FOR THE ELDERLY - Maqomam Mahmuda; Syaddam Husein M; Ardimen Ardimen (Universitas Negeri Surabaya, 2025)
An abstranct is a brief summary of a research article, thesis, review, conference This is caused by a decline in physical, psychological, economic conditions, and social interactions. This condition makes the elderly a vulnerable group who, in the context of social development, have the right to assistance. This research is a library research. Researchers obtained data for this study from various sources, including books, student scientific papers, magazines, journals, and other sources that support the results of the study. The methods used in analyzing the data obtained are interpretation, description and concluding the results of data analysis. The results of the study indicate that assistance for the elderly must refer to the needs of the elderly due to their health and physical weakness and decreased memory which triggers socio-economic problems in the elderly, found in QS. An-Nahl / 16: 70, QS. Al-Hajj/22:5, QS.ar-Rum/30: 54 and QS. An-Nur/24:60). In addition, the Qur'an also details the assistance received by the elderly, namely that it must synergize assistance from the family and the wider community as explained in QS. Al-Isra'/17: 26, QS. Yusuf/12: 78 and QS. Al-Isra'/17: 23 and QS.al-insan/76: 8. Keywords: Mentoring; Religious Counseling; Quranic Perspective; Elderly